Bridging Constitutional Regulations and International Standards in Political Finance: Preventing Electoral Corruption from a Comparative Perspective: Bridging Constitutional Regulations and International Standards in Political Finance: Preventing Electoral Corruption from a Comparative Perspective - Mad Romli; Indah Riyanti; Supaphorn Akkapin (PENA LAW: International Journal of Law, 2026)
Electoral corruption triggered by opaque political financing systems poses a serious threat to democratic integrity in many countries. Although international legal instruments such as UNCAC and GRECO guidelines have established principles of transparency and accountability, many national constitutions have not effectively adopted these norms. This study analyzes the normative and institutional gaps between constitutional regulations and international standards in political financing in five jurisdictions: Indonesia, Germany, the United States, Brazil, and South Korea. Using a legal-normative approach and comparative law methods, it finds that the absence of constitutional recognition of political financing principles weakens the effectiveness of oversight and opens space for systemic electoral corruption. This article contributes to the global discourse by proposing a hybrid legal model that combines constitutional transparency mandates, the independence of oversight institutions, and public accountability mechanisms. This study encourages the harmonization of national political financing regimes with international anti-corruption frameworks to strengthen democratic legitimacy and governance.